Peran Kemajuan Teknologi dalam Dunia Pendidikan - Anita Candra Dewi; Abdurrahman Arfah Maulana; Adelia Nururrahmah; Ahmad Ahmad; A. Muh. Farid Naufal; Muhammad Fadhil. S (Journal on Education, 2023)
Technology has brought significant changes to the world of education. The 21st century, commonly referred to as the information, globalization or digital age, has witnessed tremendous changes in education due to rapid advances in media, technology and communication. The application of technology in the context of learning has opened the door to wider access to information, increased student participation, and presented innovative teaching methods. The use of software such as online learning platforms, education-related mobile applications, and various e-learning platforms have enabled distance learning and supported self-directed learning approaches. However, there are challenges that need to be addressed including unequal access to technology, the abundance of online materials that can confuse children, and privacy and data security concerns. To optimize the educational benefits of technology, communities and education stakeholders must collaborate, along with consideration of its social and ethical impacts.